PENERAPAN METODE PEMBELAJARAN PRAKTIKUM SECARA VIRTUAL PADA MATERI PENGUKURAN DI SMA NURUL MUSLIM BATEALIT - Widiasih; Mubarok, Alfin Rizqi (Prosiding Temu Ilmiah Nasional Guru, 2023)
This research was motivated by the low learning outcomes of students in grades X-4 of SMA Nurul Muslim Batealit in the subject of Physics measurement material with calipers. In addition, the limitations of adequate experimental tools. This study was conducted in 2022 in class X-4 of Nurul Muslim High School with the number of samples in this study being 34 students with a composition of18 boys and 16 girls. The purpose of this study is to determine the improvement of learning outcomes and the adequacy of the use of learning techniques and media on student learning outcomes after the implementation of virtual-based practicum learning strategies. The method used in this study is classroom action research consisting of 2 learning improvement cycles that emphasize learningimprovement using virtual-based practicum methods. The research instrument used is in the form of teacher performance observation sheets and test questions to measure student learning outcomes. The data obtained were analyzed descriptively by comparing the initial conditions and learning conditions in each cycle. The results showed that the percentage of student learning outcomes increased from precycle to cycle II by 47%, which in the pre-cycle percentage of student learning completeness was 29% and in cycle II was 76%. So the application of virtual-based practicum methods can improve student learning outcomes in grades X-4 of SMA Nurul Muslim Batealit. For this reason, the application of virtual-based practicum methods can be applied as an alternative to other materials that require practicum and can also be applied to other schools.